Hemodynamic parameters that may predict false-lumen growth in type-B aortic dissection after endovascular repair: A preliminary study on long-term multiple follow-ups. (December 2017) - Xu, Huanming; Li, Zhenfeng; Dong, Huiwu; Zhang, Yilun; Wei, Jianyong; Watton, Paul N.; Guo, Wei; Chen, Duanduan; Xiong, Jiang
Highlights: RRT and PDiff are key parameters related to false lumen growth. Variation of RRT in short-term might be potential to predict long-term dissection growth. Largest PDiff is found where false lumen present greatest width. The first false lumen flow entry is where PDiff increases from negative to positive. Hemodynamic markers may predict false lumen growth earlier than morphological change. Abstract: Thoracic endovascular aortic repair (TEVAR) is commonly applied in type-B aortic dissection. For patients with dissection affects descending aorta and extends downward to involve abdominal aorta and possibly iliac arteries, false lumen (FL) expansion might occur post-TEVAR. Predictions of dissection development may assist in medical decision on re-intervention or surgery. In this study, two patients are selected with similar morphological features at initial presentation but with different long-term FL development post-TEVAR (stable and enlarged FL). Patient-specific models are established for each of the follow-ups. Flow boundaries and computational validations are obtained from Doppler ultrasound velocimetry. By analyzing the hemodynamic parameters, the false-to-true luminal pressure difference (PDiff) and particle relative residence time (RRT) are found related to FL remodeling. It is found that (i) the position of the first FL flow entry is the watershed of negative-and-positive PDiff and, in long-term follow-ups, and the position of largest PDiff is consistent with that of the greatest increase of FL width; (ii) high RRT occurs at the FL proximal tip and similar magnitude of RRT is found in both stable and enlarged cases; (iii) comparing to the RRT at 7days post-TEVAR, an increase of RRT afterwards in short-term is found in the stable case while a slight decrease of this parameter is found in the enlarged case, indicating that the variation of RRT in short-term post-TEVAR might be potential to predict long-term FL remodeling.